THE EXCEPTIONAL IN THE WORKS OF VAN GENNEP - Adizova Obodon Istamovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article is exceptional in the work of Van Gennep because of the breadth of historical views to which it bears witness. Indeed, we know his reluctance towards history, which is mainly due to two reasons: on the one hand, the difficulty of crossing the terra incognita which separates the end of the Roman Empire from the high middle age and on the other hand the fact that folklore is the study of living facts. Van Gennep maintained this position throughout his work and sometimes even in rather violent terms, such as when he describes the historical point of view as a “psychological and methodological disease” . It is therefore very surprising to note that, in this text, he allows himself to affirm the existence of a folkloric continuity in France from Gallo-Roman paganism until the 19th century, taking into account the contemporary stagnations or regressions of the great historical cataclysms (invasions, wars, revolutions, etc.).